Description of Socio-Emotional Development of Pre-School Children in Playgroup and Kindergarten Kusuma Putra Sidoarjo - Prameswari, Agistahani Budi; utomo, Agus setyo (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Social emotional development of children is a child's sensitivity to understand the feelings of other people when interacting in everyday life. Social emotional development of preschoolers is an important factor in forming social relationships between children and their peers. Purpose: The purpose of this study was to identify the social emotional development of preschool children in Kindergarten Kusuma Putra based on age, gender, class at school, and children's activities outside of school. Method: This research is a descriptive research with a quantitative approach. The population in this study were all parents who had pre-school aged children at Kusuma Putra Kindergarten. The data collection instrument used the PSC-17 questionnaire. The sampling technique in this study used the Total Sampling Technique with a total of 30 respondents. The data analysis used is quantitative univariate analysis. Results: In Kindergarten Kusuma Putra, it was found that 70% of the students did not experience problems in social-emotional development. However, there are 30% of children who experience disturbances in their social emotional development. Most of the children who experience social emotional development disorders are 67% of children, 56% of children at the age of 5 years and 44% of kindergarten A children. In addition there are 56% of children who often play alone tend to have disturbances in social emotional development. Conclusion: the picture of social emotional development in preschool-age children in Kindergarten Kusuma Putra is mostly without disturbances in social-emotional development. For further researchers to examine the factors that influence social emotional development in preschool children. description of social emotional development in preschool-age children in Kusuma Putra Kindergarten, most of them do not experience disturbances in social-emotional development. For further researchers to examine the factors that influence social emotional development in preschool children. description of social emotional development in preschool-age children in Kusuma Putra Kindergarten, most of them do not experience disturbances in social-emotional development. For further researchers to examine the factors that influence social emotional development in preschool children.